ACL injury risk factors & injury reduction programs in female football players - Robins, C. T. (Journal of Australian Strength and Conditioning, 2019)
Implementing neuromuscular injury reduction programs can assist in lowering the incidence of non-contact Anterior Cruciate Ligament injury in female football (soccer) players, as well as various predisposing risk factors seen within this population of athletes.